Desinformação e propagabilidade: uma análise da desordem informacional em grupos de Whatsapp - Muzell, Rodrigo Bersch (2020)
Everywhere on mass media and political conversation, the term fake news is the popular face for a problem of great complexity: informational disorder. Different sorts of issues are seen on the content spread on social media (and, more recently, in messenger apps such as WhatsApp): disinformation, incorrect or out-of-context information, often called fake news. That increase the distrust in the information we receive. This work intends to understand more about how disinformation spreads, by analyzing a group of messages that went viral on WhatsApp groups. At first, it contextualizes the research, dealing with the informational disorder and disinformation concepts, placing them in the network society and cyberculture. Next, it deals with digital social networks and the strategies that makes easier the spread of content on those mobile environments – right before looking in detail into one of them, the WhatsApp groups. Finally, performs qualitative research by making a content analysis on the most shared messages in a set of groups. This analysis shows the predominance of disinformation among the messages that have any kind of verifiable information. It also shows that the most shared disinformation pieces have certain characteristics that makes them more spreadable on social networks.